2020
DOI: 10.1002/adfm.201910503
|View full text |Cite
|
Sign up to set email alerts
|

Function Follows Form: From Semiconducting to Metallic toward Superconducting PbS Nanowires by Faceting the Crystal

Abstract: In the realm of colloidal nanostructures, with their immense capacity for shape and dimensionality control, the form is undoubtedly a driving factor for the tunability of optical and electrical properties in semiconducting or metallic materials. However, influencing the fundamental properties is still challenging and requires sophisticated surface or dimensionality manipulation. Such a modification is presented for the example of colloidal leadsulfide nanowires. It is shown that the electrical properties of le… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Surfaceinduced off-stoichiometry was already reported as a theoretical possibility for occurring midgap (surface) states at the Fermi level of PbS and the disappearance of the band gap at raising off-stoichiometry. 35,36 However, an effective passivation with surface cations reopens the band gap, 37 returning the sample its semiconducting properties. The surface bismuth in our case is linked to the PVP ligands and obviously to oxygen (Bi−O bond from XPS), and the possible dangling bonds producing metallic states are thus (at least partially) saturated.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Surfaceinduced off-stoichiometry was already reported as a theoretical possibility for occurring midgap (surface) states at the Fermi level of PbS and the disappearance of the band gap at raising off-stoichiometry. 35,36 However, an effective passivation with surface cations reopens the band gap, 37 returning the sample its semiconducting properties. The surface bismuth in our case is linked to the PVP ligands and obviously to oxygen (Bi−O bond from XPS), and the possible dangling bonds producing metallic states are thus (at least partially) saturated.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…[356] The application of soft matter for the synthesis of quantum materials in the thin film regime has already begun paying dividends, shown in earlier sections on superconductors, [114,115] topological materials, [155,165] multiferroics, [187,190] or spintronics. [79,[198][199][200]210] However, future work in this area may seek to take full advantage of the established techniques and capabilities present in soft matter thin film formation for the creation of new quantum metamaterials or devices. To begin, soft matter is already ubiquitous in nanofabrication in the form of photoresists, liftoff layers, packaging materials, and many other forms.…”
Section: Convergence In the Thin Film Regimementioning
confidence: 99%
“…In the quasi-0D regime, much work has been performed to create nanoscale superconducting objects. In many studies, quantum dot synthetic techniques have been used to create isolated nano-objects or weakly Josephson coupled arrays of superconducting lead nanocrystals, [68,[75][76][77][78] Pb/PbSe core shell particles, [79] gallium nanoclusters, [80] or palladium bismuth chalcogenide nanoparticles. [81] In much of this work, it has been found that critical field strength and critical temperature typically increase with decreasing material size until a certain material-dependent point, at which critical field, H c , and T c decrease until superconductivity is lost.…”
Section: Superconductorsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, alkali metal intercalation, substitutional doping, strain effect, and structural transformation induced metallike behavior in semiconductors but increased the scattering rate and reduced the mobility of charge carriers [6][7][8][9]. It was only recently demonstrated that metallic and superconducting phases in a semiconductor can be achieved through surface reconstruction [10]. Notwithstanding this development, realizing metal-like behavior in conventional semiconductors is still elusive.…”
Section: Introductionmentioning
confidence: 99%